A Long Non-Coding RNA of Citrus tristeza virus: Role in the Virus Interplay with the Host Immunity - Sung-Hwan Kang; Yong-Duo Sun; Osama O. Atallah; Jose Carlos Huguet-Tapia; Jerald D. Noble; Svetlana Y. Folimonova (Viruses, 2019)
During infection, Citrus tristeza virus (CTV) produces a non-coding subgenomic RNA referred to as low-molecular-weight tristeza 1 (LMT1), which for a long time has been considered as a by-product of the complex CTV replication machinery. In this study, we investigated the role of LMT1 in the virus infection cycle using a CTV variant that does not produce LMT1 (CTV-LMT1d). We showed that lack of LMT1 did not halt virus ability to replicate or form proper virions. However, the mutant virus demonstrated significantly reduced invasiveness and systemic spread in Nicotiana benthamiana as well as an inability to establish infection in citrus. Introduction of CTV-LMT1d into the herbaceous host resulted in elevation of the levels of salicylic acid (SA) and SA-responsive pathogenesis-related genes beyond those upon inoculation with wild-type (WT) virus (CTV-WT). Further analysis showed that the LMT1 RNA produced by CTV-WT or via ectopic expression in the N. benthamiana leaves suppressed SA accumulation and up-regulated an alternative oxidase gene, which appeared to mitigate the accumulation of reactive oxygen species. To the best of our knowledge, this is the first report of a plant viral long non-coding RNA being involved in counter-acting host response by subverting the SA-mediated plant defense.